Parent Care Patterns With Picky Eating Behavior In Pre-School Age - Anggun Pranessia Anggrasari (Journal of Public Health Science Research, 2020)
Pre-school age children are a time when children need adequate nutrition for children's growth and development. This is just the opposite of eating behavior in children. At that age, parents often experience difficulties in feeding. A son has been able to choose the type of meal 's what you want to consume or often (picky eating) where children can refuse to eat given, mealtime be long until more than 30 minutes, or the child will only eat certain food-only. One of the efforts to overcome the problem of picky eating in children is to apply parenting in every child's life. The purpose of this study was to identify the relationship between parenting style and picky eating behaviorin pre-school age children at TK Bahtera Mojokerto. Researchers used a correlation design with a sample size of 60 parent respondents. The instruments used were the parenting style questionnaire and the picky eating behavior questionnaire which was adapted from previous research. The results of the study using the k chi square statistical test showed a p-value of 0.001, which means that there is a relationship between parenting styles and picky eating behavior in pre-school children. The hope is that by implementing proper parenting styles from an early age, it can make children's eating habits become regular and in accordance with the Nutritional Adequacy Rate needed by preschoolers